MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS DAN SELF-CONFIDENCE MELALUI PEMBELAJARAN PEER INSTRUCTION WITH STRUCTURED INQUIRY (PISI) - Lala Naila Zamnah; Angra Meta Ruswana (Universitas Sultan Ageng Tirtayasa, 2018)
ABSTRACTThe background of this study was the students low ability of mathematical understanding and self-confidence. This study aimed at examining the enhancement of students mathematical understanding ability and self-confidence which was taught by using Peer Instruction with Structured Inquiry (PISI) compared to the students taught by using conventional learning. The design of this study was a non-equivalent control group which involved two classes. The first class were taught by using Peer Instruction with Structured Inquiry (PISI) and the second class acquired conventional learning. In obtaining the data, a mathematical understanding ability test and scala self-confidence was used as the instrument. This research was conducted to the second grade students of Mathematic Education Study Program of Galuh University in the academic year of 2016/2017. Data analysis was performed on the normalized gain of two sample groups by using a normalized mean difference test. The results showed that the learning by using Peer Instruction with Structured Inquiry (PISI) was effective in improving the students mathematical understanding ability and self-confidence. Keywords: Ability of Mathematical Understanding, Self-confidence, Peer Instruction with Structured Inquiry